The horror in the museum - Lovecraft, H. P. (Howard Phillips), 1890-1937; Jones, Stephen, 1953-; Joshi, S. T., 1958-; Derleth, August, 1909-1971; Eddy, C. M. (Clifford M.), 1896-1967 (Ballantine Books, 2007)
A collection of twenty-four short stories by the influential horror writer--either by himself or in collaboration with others--includes works of the macabre, dark fantasy, and the supernatural, appearing in their original order from the out-of-print Arkham House edition.